(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Piriformis tightness is one of the potential cause of pain, discomfort and dysfunction in community. However the ergonomic risk factors, pain (type, intensity, precipitating factors), physical anthropometrics specific to piriformis tightness were unclear. Hence the attempt was made to find the data and trends in piriformis tightness and it prevalence in bankers. Methodology: Study was conducted by approaching 36 banks in Karad taluka. Total 260 subjects (M:162;F:98) were included in the study who were assessed for there piriformis tightness by piriformis stretch test. There demographic data, no. of working years, pain (type, intensity, precipitating factor), chair height, chair width, cushion support were also documented. Result: Prevalence of piriformis tightness in bankers was 51.92%. Out of 135(M:93; F:42) bankers having tightness, 44 were having only right side involved, 22 were having left side involved and 69 were having bilateral tightness. Prevalence was more in people with BMI between 25-29kg/m2 (pre-obese) and in fourth decade of life Conclusion: Out of 260 subjects 135(51.92%) bankers were having piriformis tightness. There is increasing risk of getting piriformis tightness with increasing BMI, Age. There is not significant relation between the chair height Chair weight and Cushion support on the chair and the piriformis tightness. There was increasing pain in sitting position(after maintaining for long time) and is relieved by rest.